A Comparative Case Study of Profitability and Firm Value by Firm Characteristics - Dany Adi Saputra; Lina Nur Ardila; Vidia Ayu Satyanovi; Zulfita Fidi Astuti; Rihan Mustafa Zahri (International Journal of Economics, Business and Innovation Research, 2023)
The purpose of this case study is to describe the firm characteristics that include industry competition, debt levels, and controlling shareholder and their relation to profitability and firm value of three companies, SMGR, INTP, and SMCB, in the cement subsector listed on the Indonesia Stock Exchange in 2019. Qualitative analysis was performed by comparing profitability (return on assets, ROA), firm value (Tobin's Q), and firm value-to-profitability ratio (Q_ROA) for the three sample firms that differ in their characteristics. This case study provides the following empirical evidence. SMCB had the lowest ROA, Tobin's Q, and Q-ROA, followed by SMGR and INTP with relatively higher ROA, Tobin's Q, and Q-ROA. The level of competition in the SMCB industry is the highest, followed by INTP and SMGR. SMCB and SMGR have relatively higher DAR (greater than 45 percent) while INTP has relatively lower DAR (lower than 45 percent). The controlling shareholders of SMCB, SMGR, and INTP are national corporations, the Indonesian government, and foreign corporations, respectively. These results suggest that debt level and controlling shareholder play an important role in explaining profitability, firm value, and firm value to profitability ratio, while industrial competition has a marginal role in explaining these variables.